2019
DOI: 10.1002/wene.345
|View full text |Cite
|
Sign up to set email alerts
|

Positive water linkages of producing short rotation poplars and willows for bioenergy and phytotechnologies

Abstract: The production of short rotation woody crops (SRWCs) such as poplars and willows is a promising component of global bioenergy and phytotechnology portfolios. In addition to the provision of biomass feedstocks and pollution remediation, these trees and shrubs have been sustainably grown to conserve or utilize water in a variety of applications. Growing these woody plants for multiple uses supports many of the United Nation's Sustainable Development Goals (SDGs), especially Clean Water and Sanitation (SDG6) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…This differs from findings of Bassman and Zwier (1991) who found that T × D hybrids had higher transpiration rates than P. deltoides varietals. However, Zalesny et al (2019) found that varietals from an F1 backcross population [(T × D) × P. deltoides] tended to use less water than eastern cottonwood varietals. Eastern cottonwoods at the Coastal Plain site were intermediate and used between 600 and 800 kg water per tree during the measurement period or 320-360 mm of water over the growing season.…”
Section: Discussion Water Use Strategies -Whole Tree Water Use and Efficiencymentioning
confidence: 98%
“…This differs from findings of Bassman and Zwier (1991) who found that T × D hybrids had higher transpiration rates than P. deltoides varietals. However, Zalesny et al (2019) found that varietals from an F1 backcross population [(T × D) × P. deltoides] tended to use less water than eastern cottonwood varietals. Eastern cottonwoods at the Coastal Plain site were intermediate and used between 600 and 800 kg water per tree during the measurement period or 320-360 mm of water over the growing season.…”
Section: Discussion Water Use Strategies -Whole Tree Water Use and Efficiencymentioning
confidence: 98%
“…Instead, site effects governed substrate enzymatic digestibility (SED) and the recovery of most wood constituents ( Figure 8 ). These results are unique given the broad genetic diversity within the genus Populus [ 58 , 59 ] and, more specifically, differences between these clones for various applications, ranging from biomass to phytotechnologies [ 7 , 18 , 28 ]. It is uncommon for clonal effects to be non-existent for such poplar clones, and even more uncommon for clonal responses to their environments to be negligible [ 17 ], although geographically robust clones have been identified [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other ecosystem services are equally important. For example, poplars exhibit phreatophytic characteristics, such as high water uptake and transpiration [ 25 , 26 , 27 ] and the ability to economize water use in moisture limited areas [ 28 ]. Thus, water use efficiency (WUE), which is strongly correlated with both δ 13 C stable carbon isotope ratios and carbon isotope discrimination (Δ) [ 29 , 30 ], is an important trait during genotype selection for phytoremediation.…”
Section: Introductionmentioning
confidence: 99%
“…The development of lignocellulosic biomass to ethanol conversion pathways, high yielding willow ( Salix spp) cultivars, and commercial scale production in the Northeast US offers new opportunities for a thriving bioeconomy while providing multiple ecosystem services [ 12 , 13 ]. While there are a few studies on the life cycle GHG emissions of willow production [ 14 17 ] and its conversion into ethanol [ 18 21 ], they do not incorporate the impacts of direct land use change, the current understanding of the accumulation of willow belowground biomass and harvesting systems, and dry matter losses associated with storage, or incorporate HWE as key step in the conversion process.…”
Section: Introductionmentioning
confidence: 99%